A vulcanization accelerator based on modified lignin zinc salt and its preparation method and application

Through modified lignin zinc salt vulcanization promoters, the existing rubber sulfur vulcanization promoters exist in health and environmental risk problems, realize the efficient and environmentally friendly vulcanization effect, and improve the performance of rubber materials.

CN118221960BActive Publication Date: 2025-01-28NANJING TECH UNIV

Patent Information

Application Number
CN202410365136.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-28
Publication Date
2025-01-28
Estimated Expiration
2044-03-28

AI Technical Summary

Technical Problem

Existing rubber vulcanization accelerators have potential human health and environmental risks, and are single-function and low-efficiency, making it difficult to meet the needs of environmental protection and performance improvement.

Method used

The modified lignin zinc salt is used as a vulcanized promoter, reacts with dimipan sulfide by amino -library quality, and adds zinc -containing compound flocculation to form modified lignan zinc salt sulfur vulcanization promoters to improve the decentralization and utilization rate of zinc.

Benefits of technology

Significantly accelerate the vulcanization speed, improve the sulfurization efficiency, reduce single consumption, enhance the tensile strength and antioxidant effect of rubber materials, and reduce the amount of zinc usage and pollution risk.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118221960B_ABST
    Figure CN118221960B_ABST
Patent Text Reader

Abstract

The invention discloses a vulcanization accelerator based on modified lignin zinc salt and its preparation method and application. The modified lignin zinc salt vulcanization accelerator is prepared by the following method: reacting aminated lignin with carbon disulfide, adding a zinc-containing compound for flocculation, and the resulting precipitate is a modified lignin zinc salt vulcanization accelerator. The vulcanization accelerator of the invention can shield the hydroxyl groups and other polar groups on the surface of lignin, effectively improving the dispersibility of lignin in rubber. At the same time, since lignin is a three-dimensional network structure, zinc is loaded on its network structure, and the dispersibility of zinc is also improved, avoiding the agglomeration of zinc, and can reduce the use of zinc and reduce zinc pollution. At the same time, it can cooperate with other vulcanization aids to significantly accelerate the vulcanization speed, improve the vulcanization efficiency, reduce the unit consumption, and can improve the crosslinking density, thereby improving the tensile strength and anti-oxidation effect of the rubber material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber technology, and in particular to a vulcanization accelerator based on modified lignin zinc salt, and a preparation method and application thereof. Background Art

[0002] Lignin is the largest aromatic organic polymer compound in nature. 150 billion tons of lignin are produced every year through plant growth worldwide, second only to cellulose in agricultural and forestry biomass resources. However, lignin, which plays an important role in plant growth and development, is only used as a by-product of wood hydrolysis and papermaking in industrial production, and has not been fully utilized, but has caused serious pollution of water and soil. Developing high-value-added functional materials from low-cost and widely available industrial lignin can not only reduce corporate production costs and reduce environmental pollution, but also conform to the development trend of high-performance, multifunctional and green new materials in my country, and is of great significance in promoting the ecological utilization of renewable resources and alleviating the shortage of petrochemical resources.

[0003] Lignin is abundant in nature, and its molecular structure contains a large number of active functional groups such as aromatic groups, phenolic hydroxyl groups, alcoholic hydroxyl groups, carbonyl groups, methoxy groups, carboxyl groups, double bonds, etc. Therefore, the development of functional materials using lignin has always attracted the attention of researchers. In recent years, researchers have been committed to studying high-performance, low-cost lignin-modified materials or chemicals through chemical reactions, composite modifications, etc., or to producing important chemical raw materials through designable degradation methods.

[0004] Zinc oxide is one of the most widely used additives in rubber products. It is not only used as an activator for the rubber sulfur vulcanization system, but also can improve the heat resistance and thermal conductivity of rubber, and has a whitening effect. As one of the most important steps in the rubber processing and forming process, rubber vulcanization directly affects the performance of rubber products. Compared with sulfur alone, a small amount of accelerator combined with sulfur can greatly increase the vulcanization rate and improve the performance of vulcanized rubber. Since zinc is a heavy metal, when zinc enters the soil with the ground rubber crumbs and accumulates, it will pollute the soil. With the increasing environmental protection requirements, it is imperative to reduce the use of zinc in rubber products.

[0005] At present, rubber vulcanization accelerators generally have potential human health and environmental risk problems, and at the same time, the vulcanization accelerator efficiency is low and the function is single. Therefore, the development of non-toxic, zinc oxide-free or low-zinc oxide, efficient and multifunctional new vulcanization accelerators is of great significance to the rubber industry. For example, Chinese invention CN113929608 A discloses a method for preparing a vulcanization accelerator, comprising the following steps: adding carbon disulfide to a mixed aqueous solution of selenium oxide and glutamic acid, and reacting to obtain a vulcanization accelerator, but the cost is high and the vulcanization efficiency is not high, which still needs to be improved. For example, nano zinc oxide replaces traditional zinc oxide, organic zinc complexes replace zinc oxide, nano inorganic filler zinc-carrying technology, and the development of other divalent metal oxide activators and rare earth multifunctional rubber vulcanizers. Since it is the zinc ions that actually play an activating role in the vulcanization process, the traditional zinc oxide activated vulcanization reaction is actually an interfacial reaction, and only the zinc ions on the surface of the zinc oxide can play a role, and a large number of zinc ions inside are still bound in the zinc oxide lattice, so most of the zinc oxide cannot be fully utilized, which will cause great waste. Therefore, the present invention provides a vulcanization accelerator based on modified lignin zinc salt, and a preparation method and application thereof. Summary of the invention

[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a vulcanization accelerator based on modified lignin zinc salt and its preparation method and application in view of the shortcomings of the prior art.

[0007] In order to solve the above technical problems, the present invention discloses the following technical solutions:

[0008] In a first aspect, the present invention discloses a vulcanization accelerator based on modified lignin zinc salt, which is prepared by the following method: reacting aminated lignin with carbon disulfide, then adding a zinc-containing compound for flocculation, and the resulting precipitate is the modified lignin zinc salt vulcanization accelerator.

[0009] In some embodiments, the modified lignin zinc salt-based vulcanization accelerator is as shown in Formula I; S and Zn are bound by metal chelation;

[0010]

[0011] In a second aspect, the present invention discloses a method for preparing a vulcanization accelerator based on modified lignin zinc salt, comprising: reacting aminated lignin with carbon disulfide, and then adding a zinc-containing compound for flocculation, and the resulting precipitate is a modified lignin zinc salt vulcanization accelerator.

[0012] In the above first and second aspects,

[0013] The preparation method of the aminated lignin comprises adding an amine compound and an aldehyde compound to a liquid containing lignin substances for reaction; the liquid containing lignin substances is a liquid containing one or more of lignin, lignin sulfonate or lignin derivatives; the pH of the liquid containing lignin substances is 10-14, preferably 11-13; preferably, the concentration of lignin substances in the liquid containing lignin substances is 35-45 mg / mL; the amine compound comprises methylamine, ethylamine, propylamine, butylamine, pentylamine, ethanolamine, sec-butylamine, octadecylamine, cis-oleyl primary amine any one or more combinations thereof; preferably, the aldehyde compound includes formaldehyde; the molar ratio of the lignin, the amine compound and the aldehyde compound is 1:0.5-1.5:0.5-1.5, preferably 1:1:1; further, the liquid containing the lignin substance is heated to 65-75°C, the amine compound is added and stirred sufficiently, and then the aldehyde compound is added to react; preferably, the reaction temperature is 65-75°C, and the reaction time is 3.5-4.5h; preferably, the reaction is carried out under stirring; preferably, the stirring rate is 200-400rpm.

[0014] Wherein, the mass ratio of the aminated lignin to carbon disulfide is 1:0.5-1.5, preferably 1:1.

[0015] Wherein, the zinc-containing compound is selected from any one or more combinations of zinc sulfate, zinc chloride, zinc nitrate and zinc acetate.

[0016] Wherein, the zinc-containing compound is added in the form of a zinc-containing compound solution, and the mass fraction of the zinc-containing compound solution is 10%-15%, preferably 10%.

[0017] The molar volume ratio of the aminated lignin to the zinc-containing compound solution is 1 mol: 6.3-10.3 L, preferably 1 mol: 7.3-9.3 L.

[0018] Wherein, the reaction temperature is 35-45°C, and the reaction time is 3.5-4.5h.

[0019] In a third aspect, the present invention discloses the use of a vulcanization accelerator based on modified lignin zinc salt described in the first aspect and a vulcanization accelerator based on modified lignin zinc salt prepared by the method described in the second aspect in the preparation of rubber materials.

[0020] Wherein, the weight of the modified lignin zinc salt vulcanization accelerator is 5-10 parts per 100 parts of rubber.

[0021] The rubber material is made of the following components in parts by weight: 100 parts of rubber, 40-50 parts of carbon black, 5-10 parts of modified lignin zinc salt vulcanization accelerator, 1-3 parts of stearic acid, 3-5 parts of zinc oxide, and 2-3 parts of vulcanizing agent.

[0022] Wherein, the method for preparing the rubber material comprises:

[0023] (1) Weighing each component according to the formula ratio, firstly mixing rubber, zinc oxide, stearic acid, carbon black, and modified lignin zinc salt vulcanization accelerator;

[0024] (2) adding a vulcanizing agent to the rubber mixture obtained in step (1) by open refining, and thinning and triangle bagging;

[0025] (3) vulcanizing the mixed rubber obtained in step (2) to obtain the rubber material.

[0026] In summary, the present invention provides a new vulcanization accelerator, a lignin zinc salt complex, which increases the dispersibility of zinc in the rubber matrix by loading zinc in the three-dimensional network structure of lignin, avoids zinc agglomeration, and also improves the dispersibility of lignin in the rubber matrix.

[0027] Beneficial effects:

[0028] (1) The present invention uses lignin as raw material, which is cheap, readily available, and renewable, and can effectively save resources and protect the environment.

[0029] (2) The vulcanization accelerator of the present invention is an accelerator based on modified lignin zinc salt, which can cooperate with other vulcanization aids to significantly accelerate the vulcanization speed, improve the vulcanization efficiency, reduce the unit consumption, and increase the crosslinking density, thereby improving the tensile strength and antioxidant effect of the rubber material.

[0030] (3) The vulcanization accelerator of the present invention can shield the hydroxyl groups and other polar groups on the surface of lignin, effectively improving the dispersibility of lignin in rubber. At the same time, since lignin has a three-dimensional network structure, zinc is loaded on its network structure, and the dispersibility of zinc is also improved, thereby avoiding the agglomeration of zinc, reducing the amount of zinc used, and reducing zinc pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0032] Figure 1 These are infrared spectra of original lignin (L), prepared aminated lignin (AL), and modified lignin zinc salt (AL-S) vulcanization accelerator.

[0033] Figure 2 The thermogravimetric curves of the original lignin (L), the prepared aminated lignin (AL), and the modified lignin zinc salt (AL-S) vulcanization accelerator. DETAILED DESCRIPTION

[0034] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0035] In the following examples, unless otherwise specified, the concentration of the formaldehyde solution is 38%.

[0036] In the following examples, unless otherwise specified, the zinc sulfate solutions are all 10% by mass aqueous solutions.

[0037] In the following examples, unless otherwise specified, the molecular weight of the industrial lignin is 2276 g / mol, and the molar weight of 20 g of industrial lignin is 0.0088 mol.

[0038] Embodiment 1:

[0039] (1) Add 20 g of industrial lignin to 480 ml of pure water, add an appropriate amount of NaOH to adjust the solution pH to 12 and stir until dissolved, pour the lignin alkaline solution into a three-necked flask and stir, heat to 70°C, add butylamine, stir thoroughly, and then slowly add formaldehyde solution to start the reaction. The reaction speed is 300 r / min and the reaction time is 4 h (the molar ratio of lignin, butylamine and formaldehyde is 1:1:1), to obtain a reaction solution containing aminated lignin.

[0040] (2) The reaction solution containing aminated lignin obtained in step (1) was cooled to 40°C and slowly CS2 was added, the reaction speed was 300r / min, and the reaction time was 4h. Stirring was continued, and 50ml of 10% zinc sulfate solution was added for flocculation, filtered, the filter cake was washed with water, dried (the drying temperature of the blast dryer was 60°C, the time was 24h), and air flow pulverized to obtain about 22g of modified lignin zinc salt vulcanization accelerator with a particle size of 2-3μm (the mass ratio of industrial lignin to CS2 was 1:1).

[0041] (3) 100 parts of natural rubber, 1 part of stearic acid, 3 parts of zinc oxide, 40 parts of carbon black, and 5 parts of modified lignin zinc salt vulcanization accelerator were accurately weighed and added into an internal mixer in sequence, and kneaded at 60°C for 8 minutes.

[0042] (4) Add the rubber mixture obtained in step (3) to the roll of an open mixing mill, add 2 parts of sulfur and mix at 20° C. for 6 minutes, and then thinly pass and triangle-wrap the mixture.

[0043] (5) vulcanizing the rubber mixture obtained in step (4) at 151° C. to obtain the rubber material.

[0044] pass Figure 1 Infrared spectra of the original lignin (L), the prepared aminated lignin (AL), and the modified lignin zinc salt (AL-S) vulcanization accelerator. -1 、750cm -1 Two new peaks appeared, 1260 cm -1 The absorption peak at 2930cm -1 The absorption peak at 750cm is enhanced, which is caused by the stretching vibration of CH2, mainly affected by the methylene group in butylamine. -1 The new peaks that appeared were the stretching vibrations of the C=S and CS bonds, indicating that the grafting was successful.

[0045] pass Figure 2 The thermogravimetric curves of the original lignin (L) and the prepared aminated lignin (AL) and the modified lignin zinc salt (AL-S) vulcanization accelerator are compared. Compared with L in the range of 0-750°C, the thermal stability of AL is improved to a certain extent, and above 750°C, the difference between the two is not large; and compared with AL and L in general, the thermal stability of AL-S is significantly improved.

[0046] Embodiment 2:

[0047] (1) Add 20 g of industrial lignin to 480 ml of pure water, add an appropriate amount of NaOH to adjust the solution pH to 12 and stir until dissolved, pour the lignin alkaline solution into a three-necked flask and stir, heat to 70°C, add butylamine, stir thoroughly, and then slowly add formaldehyde solution to start the reaction. The reaction speed is 300 r / min and the reaction time is 4 h (the molar ratio of lignin, butylamine and formaldehyde is 1:1:1), to obtain a reaction solution containing aminated lignin.

[0048] (2) The reaction solution containing aminated lignin obtained in step (1) was cooled to 40°C and slowly CS2 was added, the reaction speed was 300r / min, and the reaction time was 4h. Stirring was continued, and 50ml of 10% zinc sulfate solution was added for flocculation, filtered, the filter cake was washed with water, dried (the drying temperature of the blast dryer was 60°C, the time was 24h), and air flow pulverized to obtain a modified lignin zinc salt vulcanization accelerator with a particle size of 2-3μm (the mass ratio of industrial lignin to CS2 was 1:1).

[0049] (3) 100 parts of natural rubber, 1 part of stearic acid, 3 parts of zinc oxide, 40 parts of carbon black, and 10 parts of modified lignin zinc salt vulcanization accelerator were accurately weighed and added into an internal mixer in sequence, and kneaded at 60°C for 8 minutes.

[0050] (4) Add the rubber mixture obtained in step (3) to the roll of an open mixing mill, add 2 parts of sulfur and mix at 20° C. for 6 minutes, and then thinly pass and triangle-wrap the mixture.

[0051] (5) vulcanizing the rubber mixture obtained in step (4) at 151° C. to obtain the rubber material.

[0052] Embodiment 3:

[0053] (1) Add 20 g of industrial lignin to 480 ml of pure water, add an appropriate amount of NaOH to adjust the solution pH to 12 and stir until dissolved, pour the lignin alkaline solution into a three-necked flask and stir, heat to 70°C, add ethanolamine, stir thoroughly, and then slowly add formaldehyde solution to start the reaction. The reaction speed is 300 r / min and the reaction time is 4 h (the molar ratio of lignin, ethanolamine and formaldehyde is 1:1:1), to obtain a reaction solution containing aminated lignin.

[0054] (2) The reaction solution containing aminated lignin obtained in step (1) was cooled to 40°C and slowly CS2 was added, the reaction speed was 300r / min, and the reaction time was 4h. Stirring was continued, and 50ml of 10% zinc sulfate was added for flocculation, and the mixture was filtered, the filter cake was washed with water, dried (the drying temperature of the blast dryer was 60°C, and the time was 24h), and air flow pulverized to obtain a modified lignin zinc salt vulcanization accelerator with a particle size of 2-3μm (the mass ratio of industrial lignin to CS2 was 1:1).

[0055] (3) 100 parts of natural rubber, 1 part of stearic acid, 3 parts of zinc oxide, 40 parts of carbon black, and 5 parts of modified lignin zinc salt vulcanization accelerator were accurately weighed and added into an internal mixer in sequence, and kneaded at 60°C for 8 minutes.

[0056] (4) Add the rubber mixture obtained in step (3) to the roll of an open mixing mill, add 2 parts of sulfur and mix at 20° C. for 6 minutes, and then thinly pass and triangle-wrap the mixture.

[0057] (5) vulcanizing the rubber mixture obtained in step (4) at 151° C. to obtain the rubber material.

[0058] Embodiment 4:

[0059] (1) Add 20 g of industrial lignin to 480 ml of pure water, add an appropriate amount of NaOH to adjust the solution pH to 12 and stir until dissolved, pour the lignin alkaline solution into a three-necked flask and stir, heat to 70°C, add ethanolamine, stir thoroughly, and then slowly add formaldehyde solution to start the reaction. The reaction speed is 300 r / min and the reaction time is 4 h (the molar ratio of lignin, ethanolamine and formaldehyde is 1:1:1), to obtain a reaction solution containing aminated lignin.

[0060] (2) The reaction solution containing aminated lignin obtained in step (1) was cooled to 40°C and slowly CS2 was added, the reaction speed was 300r / min, and the reaction time was 4h. Stirring was continued, and 50ml of 10% zinc sulfate was added for flocculation, and the mixture was filtered, the filter cake was washed with water, dried (the drying temperature of the blast dryer was 60°C, and the time was 24h), and air flow pulverized to obtain a modified lignin zinc salt vulcanization accelerator with a particle size of 2-3μm (the mass ratio of industrial lignin to CS2 was 1:1).

[0061] (3) 100 parts of natural rubber, 1 part of stearic acid, 3 parts of zinc oxide, 40 parts of carbon black, and 10 parts of modified lignin zinc salt vulcanization accelerator were accurately weighed and added into an internal mixer in sequence, and kneaded at 60°C for 8 minutes.

[0062] (4) Add the rubber mixture obtained in step (3) to the roll of an open mixing mill, add 2 parts of sulfur and mix at 20° C. for 6 minutes, and then thinly pass and triangle-wrap the mixture.

[0063] (5) vulcanizing the rubber mixture obtained in step (4) at 151° C. to obtain the rubber material.

[0064] Comparative Example 1: Unmodified industrial lignin

[0065] (1) 100 parts of natural rubber, 1 part of stearic acid, 3 parts of zinc oxide, 40 parts of carbon black, and 5 parts of unmodified industrial lignin were accurately weighed and added into an internal mixer in sequence, and kneaded at 60°C for 8 minutes.

[0066] (2) The rubber mixture obtained in step (1) is added to the roll of an open mixing mill, 2 parts of sulfur is added, and mixed at 20° C. for 6 minutes, and then thinned and triangularly packaged.

[0067] (3) vulcanizing the rubber mixture obtained in step (2) at 151° C. to obtain the rubber material.

[0068] Comparative Example 2: No vulcanization accelerator added

[0069] (1) 100 parts of natural rubber, 1 part of stearic acid, 3 parts of zinc oxide, and 40 parts of carbon black were accurately weighed and added to an internal mixer in sequence, and kneaded at 60°C for 8 minutes.

[0070] (2) The rubber mixture obtained in step (1) is added to the roll of an open mixing mill, 2 parts of sulfur is added, and mixed at 20° C. for 6 minutes, and then thinned and triangularly packaged.

[0071] (3) vulcanizing the rubber mixture obtained in step (2) at 151° C. to obtain the rubber material.

[0072] Comparative Example 3: Replace the vulcanization accelerator with accelerator DM (i.e. 2,2'-dibenzothiazole disulfide)

[0073] (1) 100 parts of natural rubber, 1 part of stearic acid, 3 parts of zinc oxide, and 40 parts of carbon black were accurately weighed and added to an internal mixer in sequence, and kneaded at 60° C. for 8 minutes;

[0074] (2) The rubber mixture obtained in step (2) is added to the roll of the open mixing mill, 2 parts of sulfur and 2 parts of vulcanization accelerator DM are added, mixed at 20° C. for 6 min, and thin-passed and triangle-wrapped.

[0075] (3) vulcanizing the rubber mixture obtained in step (2) at 151° C. to obtain the rubber material.

[0076] The above embodiments and comparative examples are tested:

[0077] (1) Elemental analysis tests were performed on the original lignin and the prepared vulcanization accelerator.

[0078] (2) Vulcanization characteristics test, tested by a rotorless vulcanizer.

[0079] (3) Mechanical properties test, the test content and methods are as follows:

[0080] Performance of vulcanized rubber - vulcanization characteristics: test method see GB / T 16584-1996;

[0081] Tensile strength: test method see GB / T 528-2009;

[0082] Elongation at break: test method see GB / T 528-2009;

[0083] Tensile stress: test method see GB / T 528-2009;

[0084] Tested by electronic universal testing machine.

[0085] (4) Oxidation induction time test: The prepared rubber material is tested by a differential calorimeter. The test method is shown in GB / T 19466.6-2009.

[0086] The experimental results are as follows:

[0087] 1. Elemental analysis

[0088] Table 1 Elemental analysis of the vulcanization accelerators prepared in Examples 2-4 and the original lignin

[0089] name C(%) H(%) N(%) S(%) Original lignin 62.66 5.22 0.25 0.27 Example 2 50.19 5.19 5.25 8.32 Example 3 52.51 5.32 4.88 8.14 Example 4 50.35 5.42 5.12 8.24

[0090] As shown in Table 1, the N and S contents of the original lignin were measured to be 0.25% and 0.27%, while the N and S contents of the modified lignin zinc salt vulcanization accelerator were significantly improved, reaching 19.52-21 times and 30.15-30.82 times of the original lignin, respectively. This result shows that the -NH- and -CS2- groups were successfully grafted to the lignin.

[0091] 2. Rubber vulcanization characteristics

[0092] Table 2 Rubber vulcanization characteristics of Examples 1-3 and Comparative Examples 1-2

[0093] MH (dN·m) ML (dN·m) Tc10(min) Tc90(min) Example 1 15.21 1.25 1.53 10.31 Example 2 17.12 1.19 1.96 6.59 Example 3 14.25 1.24 1.45 13.52 Example 4 17.02 1.18 1.79 7.46 Comparative Example 1 11.56 1.32 1.84 23.72 Comparative Example 2 11.28 1.15 1.26 20.84 Comparative Example 3 13.52 1.35 1.42 15.61

[0094] As can be seen from Table 2, compared with Comparative Example 3, the vulcanization rate and torque of Examples 1-4 are significantly improved compared with Comparative Example 3, and the effect is more obvious with the increase of the amount of the modified lignin zinc salt vulcanization accelerator; compared with Comparative Example 1, the Tc90 of the unmodified lignin is extended in Example 1, that is, the unmodified lignin delays the vulcanization rate. The vulcanization efficiency of the present invention is also improved compared with the traditional vulcanization accelerator (DM).

[0095] 3. Mechanical properties of rubber

[0096] Table 3 Rubber mechanical properties of Examples 1-3 and Comparative Examples 1-2

[0097] Tensile strength(MPa) Elongation at break (%) 100% tensile stress (MPa) Example 1 25.62 434 4.24 Example 2 27.55 445 4.85 Example 3 24.62 425 4.02 Example 4 27.12 440 4.82 Comparative Example 1 20.43 386 3.41 Comparative Example 2 18.15 377 3.22 Comparative Example 3 24.83 424 3.98

[0098] As can be seen from Table 3, compared with Comparative Examples 1-2, Examples 1-4 have improved mechanical properties, especially tensile strength; as the amount of modified lignin zinc salt vulcanization accelerator increases, the improvement effect becomes more obvious. Compared with the traditional vulcanization accelerator (DM), the present invention improves the mechanical properties of rubber, effectively improves the dispersibility of fillers in rubber, and improves the mechanical properties of rubber.

[0099] 4. Rubber oxidation induction time

[0100] Table 4 Rubber oxidation induction time of Examples 1-3 and Comparative Examples 1-2

[0101] Oxidation induction time (min) Example 1 33 Example 2 37 Example 3 30 Example 4 35 Comparative Example 1 26 Comparative Example 2 22 Comparative Example 3 24

[0102] It can be seen from the table that compared with comparative examples 1-3, the oxidation induction time of the rubber added with the new vulcanization accelerator in Examples 1-4 is much higher than that without the addition, and the more the addition amount, the higher the oxidation induction time and the better the antioxidant effect of the rubber.

[0103] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. Application of a vulcanization accelerator based on modified lignin zinc salt in the preparation of rubber materials, characterized in that: The preparation method is as follows: the aminated lignin is reacted with carbon disulfide, and then a zinc-containing compound is added for flocculation, and the obtained precipitate is a modified lignin zinc salt vulcanization accelerator.

2. The use according to claim 1, characterized in that: The method for preparing the aminated lignin comprises adding an amine compound and an aldehyde compound into a liquid containing lignin substances for reaction.

3. The use according to claim 2, characterized in that: The pH of the liquid containing lignin substances is 10-14, and the concentration of lignin substances in the liquid containing lignin substances is 35-45 mg / mL.

4. The use according to claim 2, characterized in that: The amine compounds include any one or more combinations of methylamine, ethylamine, propylamine, butylamine, pentylamine, ethanolamine, sec-butylamine, octadecylamine, and cis-oleyl primary amine; and the aldehyde compounds include formaldehyde.

5. The use according to claim 2, characterized in that: The molar ratio of the lignin, the amine compound and the aldehyde compound is 1:0.5-1.5:0.5-1.

5.

6. The use according to claim 2, characterized in that: The liquid containing lignin is heated to 65-75°C, an amine compound is added and stirred thoroughly, and then an aldehyde compound is added to react.

7. The use according to claim 2, characterized in that: The reaction temperature is 65-75°C, and the reaction time is 3.5-4.5h.

8. The use according to claim 2, characterized in that: The reaction is carried out under stirring at a rate of 200-400 rpm.

9. The use according to claim 1, characterized in that: The mass ratio of the aminated lignin to carbon disulfide is 1:0.5-1.5, and the zinc-containing compound is selected from any one or more combinations of zinc sulfate, zinc chloride, zinc nitrate and zinc acetate.

10. The use according to claim 1, characterized in that: The zinc-containing compound is added in the form of a zinc-containing compound solution, and the mass fraction of the zinc-containing compound solution is 10%-15%.

11. The use according to claim 10, wherein the molar volume ratio of the aminated lignin to the zinc-containing compound solution is 1 mol: 6.3-10.3 L.

12. The use according to claim 10, wherein the molar volume ratio of the aminated lignin to the zinc compound solution is 1 mol: 7.3-9.3 L.

13. The use according to claim 1, characterized in that: The reaction temperature is 35-45°C, and the reaction time is 3.5-4.5h.

14. The use according to claim 1, characterized in that: The weight of the vulcanization accelerator based on modified lignin zinc salt is 5-10 parts per 100 parts of rubber.

15. The use according to claim 1, characterized in that: The rubber material is made of the following components in parts by weight: 100 parts of rubber, 40-50 parts of carbon black, 5-10 parts of modified lignin zinc salt vulcanization accelerator, 1-3 parts of stearic acid, 3-5 parts of zinc oxide, and 2-3 parts of vulcanizing agent.

Citation Information

Patent Citations

  • Vulcanization accelerator as well as preparation method and application thereof

    CN113929608A

  • Lignin zinc salt compound, preparation method, application, rubber composition and tire

    CN115678038A

Cited By

  • Safe and non-toxic vulcanization accelerator for rubber and preparation process thereof

    CN121673650A

  • Safe and non-toxic vulcanization accelerator for rubber and preparation process thereof

    CN121949811A